Penggunaan Nessus dalam Mengidentifikasi Kerentanan Keamanan pada Perangkat Komputer - Rizky, Alif; Servanda, Yustian (Jurnal Sains dan Teknologi (JSIT), 2024)
Information system security is one of the many things that must be considered in information technology management. Computer devices that have security vulnerabilities can provide loopholes that can be used by irresponsible parties to hack and carry out other illegal activities on vulnerable computers. Nessus is a security tool that can be used to identify vulnerabilities on computer devices. This testing aims to test the ability of Nessus as a tool used to identify vulnerabilities on computer devices. The research method used is Vulnerability Assessment. The collected data includes the types of identified vulnerabilities, the severity level of the vulnerabilities, and an explanation of the successfully identified vulnerabilities. The research results show that Nessus effectively identifies various types of security vulnerabilities on computer devices, including vulnerabilities in operating systems, applications, and configurations. Nessus can also assist in the mitigation process by providing recommendations for improvements that can be made. This research concludes that the use of Nessus can improve the security of computer devices.